2002
DOI: 10.1002/j.1551-8833.2002.tb09512.x
|View full text |Cite
|
Sign up to set email alerts
|

Removing oils FROM WATER with organoclays

Abstract: Organically modified clays have long been used by industry to remove oil from water. A study was undertaken to verify results from real‐world applications and develop a better understanding of the chemical conditions under which organoclays are most effective. Systematic testing was conducted on some 50 oils, including mineral oils, vegetable oils, animal fats, fish oils, and synthetic oils. In addition, the adsorption capacity of activated carbon was tested in order to compare the effectiveness of the two med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…The objective of this work is the study of the adsorption of the paranitrophenol on an organoclay synthesised by using a surfactant molecule with two alkyl chains. This study is of great importance for understanding the structure, properties, and potential applications of these types of organoclays, especially in water purification [1][2][3][4][5]7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of this work is the study of the adsorption of the paranitrophenol on an organoclay synthesised by using a surfactant molecule with two alkyl chains. This study is of great importance for understanding the structure, properties, and potential applications of these types of organoclays, especially in water purification [1][2][3][4][5]7 …”
Section: Introductionmentioning
confidence: 99%
“…Many of these molecules are recalcitrant and difficult to remove through oxidation or photocatalytic oxidation using, for example, hydrogen peroxide and intense UV radiation. One method for purifying water is to use organoclays [1][2][3][4][5]. These organoclays are prepared by ion exchange of the cation in the swelling clay such as montmorillonite with a cation surfactant [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported on the effectiveness of modified clays in the treatment of contaminants (e.g. Alther, 2002a;2002b;Faschan, 1992;LaGrega et al, 2001;Montgomery et al, 1991). Modified clays have been successfully used in some of the UK commercial projects mentioned above: West Drayton site project (Evans and AlTabbaa, 1999), Long Eaton, Nottingham (Al-Tabbaa and Evans, 2003) and the Sir John Rogerson's quay, Dublin (Evans, 2005).…”
Section: Modified Claysmentioning
confidence: 95%
“…Quaternary ammonium salts have also been used to modify cellulose surfaces [29]. Furthermore, the use of surfactant treated materials to remove oil-in-water has been investigated such as wheat straw and organoclay [30]. Chemical functionalization of the biomass surface by a cationic surfactant is carried out to introduce stable positive electrostatic charges on the surface to obtain better dispersion, and tune its surface energy characteristics to improve compatibility, especially when used in conjunction with nonpolar or hydrophobic materials [31].…”
Section: Introductionmentioning
confidence: 99%